Constructing Digital Public Service Democracy in the Era of the COVID-19 Pandemic in Indonesia - Herwanto, Trisno Sakti (KnE Social Sciences, 2022)
The purpose of this paper was to reconstruct the practice of digital-based public service democracy, particularly in the context of the COVID-19 pandemic. It is commonly assumed that service democracy places a high value on users and citizens. Furthermore, in the context of public services, democracy should be directed at the public, which includes all stakeholders with an interest in and a role in service delivery. This paper examined the findings of two previous research studies on digital public services in the era before and after the COVID-19 pandemic, based on this understanding. According to the findings of the analysis, the current digital public service democracy is still more focused on service users than on other stakeholders. A solution is proposed in the form of strengthening public service providers’ human resources capacity as one of the keys to the success of digital public service democracy. Internalizing public service motivation, ethics, and culture must become a basic competency for civil servants providing digital services. Thus, digital public service democracy requires a greater focus on the role of each stakeholder. Keywords: digital public service democracy, digital services, COVID-19 pandemic